2021
DOI: 10.3390/applmicrobiol1010012
|View full text |Cite
|
Sign up to set email alerts
|

S. epidermidis Isolates from a Tertiary Care Portuguese Hospital Show Very High Antibiotic Non-Susceptible Rates and Significant Ability to Form Biofilms

Abstract: Healthcare-associated infections (HAIs) have been increasing during recent decades, leading to long hospital stays and high morbidity and mortality rates. The usage of antibiotics therapy against these infections is enhancing the emergence of more multiple-drug resistant strains, in particular in Staphylococcus epidermidis. Hence, this study focused on the resistance pattern of S. epidermidis isolates from clinical settings and its association with phenotypic and molecular traits. Our results showed that HAIs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 51 publications
2
6
0
Order By: Relevance
“…Which shows that pediatric age group especially infants are at higher risk of infections with S. epidermidis. Similar results were observed in study conducted by Lopes N et al 13 who isolated 24.4% of S. epidermidis isolates from children less 1 year of age group. Male preponderance is observed in the present study similar to the study done by Lopes N et al 13 S. epidermidis is isolated from all type of clinical samples of which maximum of isolates were recovered from pus samples (34.67%) followed by Blood (25.33%).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Which shows that pediatric age group especially infants are at higher risk of infections with S. epidermidis. Similar results were observed in study conducted by Lopes N et al 13 who isolated 24.4% of S. epidermidis isolates from children less 1 year of age group. Male preponderance is observed in the present study similar to the study done by Lopes N et al 13 S. epidermidis is isolated from all type of clinical samples of which maximum of isolates were recovered from pus samples (34.67%) followed by Blood (25.33%).…”
Section: Discussionsupporting
confidence: 90%
“…Similar results were observed in study conducted by Lopes N et al 13 who isolated 24.4% of S. epidermidis isolates from children less 1 year of age group. Male preponderance is observed in the present study similar to the study done by Lopes N et al 13 S. epidermidis is isolated from all type of clinical samples of which maximum of isolates were recovered from pus samples (34.67%) followed by Blood (25.33%). Pus sample is the leading source of S. epidermidis in the studies conducted by Jayanthi RS et al (30.11%) 14 and Choudary U et al (30.12%) 15 and blood is second most common sample in a study conducted by Jayanthi RS et al (22.59%).…”
Section: Discussionsupporting
confidence: 90%
“…The increasing resistance to antibiotics, within the hospital and in the community, is seriously compromising our ability to treat LOS, with CoNS being increasingly resistant to a plethora of antibiotics, especially against beta-lactam antibiotics and, more importantly, frequently presenting multi-drug resistance phenotypes (resistant to 3 or more classes of antibiotics) [ 283 , 284 , 285 ]. Among S. epidermidis neonatal isolates, epidemiological studies have reported that ~52.7–85% present a multi-drug resistance profile, with ~92–99% resistant to penicillin and ~70–78% to gentamicin [ 43 , 286 , 287 ]. In the case of S. haemolyticus , the studies performed showed that ~82–87% of the isolates are multi-drug resistant, with 90% of the isolates being resistant to penicillin and ~61–79% to gentamycin [ 44 , 287 , 288 ].…”
Section: Los Diagnosis and Treatmentmentioning
confidence: 99%
“…This clone has shown high resistance to penicillin (99%), methicillin (95.6%) and gentamicin (95.1%) [ 38 ]. With regards to vancomycin, all the S. epidermidis and S. haemolyticus neonatal isolates studied so far have shown 100% susceptibility to vancomycin [ 43 , 286 , 289 ]. However, in the case of S. capitis neonatal isolates, in particular, the ones belonging to the NRCS-A clone showed resistance (37.5%) or heteroresistance (62.5%) to vancomycin [ 38 ].…”
Section: Los Diagnosis and Treatmentmentioning
confidence: 99%
“…One bacterial colony of each isolate was inoculated into 50 µL of nuclease-free water and lysed by heating at 98 • C for 10 min. After centrifugation at maximum speed for 5 min, 3 µL of the collected supernatant were used as a template for PCR amplification, as previously described [29]. The primer sequences used in this study are listed in Supplementary Table S1.…”
Section: Presence Of Aap and Agrb Genes Among Clinical S Epidermidis ...mentioning
confidence: 99%